The Analogous usage of pathos in al-Musāmiḥ Karīm TV program - Chaari, Imen (International Journal of Linguistics and Translation Studies, 2024)
Social TV programs like al-Musāmiḥ Karīm TV program and ‘Andī Mānqulik receive a huge success. Sigma’s statistics shows the high percentage of viewing of ‘Andī Mānqulik (11.7%) and al-Musāmiḥ Karīm (24.7%). Aiming to shed light on the factors that contribute to this high percentage, this piece of research attempts to enter the TV program al-Musāmiḥ Karīm into the domain of linguistic analysis. Al-Musāmiḥ Karīm proportion of viewing, which is the highest proportion, mirrors the success of this program in affecting its viewers (African Manager). Through targeting the emotions of the viewers, al-Musāmiḥ Karīm manages to attract the attention of the audience. This paper argues that in al-Musāmiḥ Karīm TV program there is the use of analogy. In this respect, the TV presenter and the guest use the same rhetorical strategies to affect the audience. In other words, they choose certain rhetorical strategies that pertain to the realm of pathos to make the audience sympathize with their stories. It should be noted that in this article the term analogy is not used in the deep sense. In other words, this paper is supposed to analyze the surface meaning of analogy. In this regard, analogy is defined as “a comparison of two things based on their being alike in some way” (Meriam-Webster dictionary)